Functional Characterization of Genes Coding for Novel β-D-Glucosidases Involved in the Initial Step of Secoiridoid Glucosides Catabolism in Centaurium erythraea Rafn - Božunović, Jelena; Milutinović, Milica; Aničić, Neda; Skorić, Marijana; Matekalo, Dragana; Živković, Suzana; Dragićević, Milan; Filipović, Biljana; Banjanac, Tijana; Petrović, Luka; Mišić, Danijela (Frontiers in Plant Science, 2022)
Secoiridoid glucosides (SGs) are monoterpenoids derived from the iridoid cyclopentan-C-pyran skeleton with -D glucose linked at C1 position. Coordinated metabolic processes, such as biosynthesis and catabolism of SGs, ensure constitutive presence of these bitter tasting compounds in plant tissues, which plays a decisive role in the defence against pathogens and herbivores. These compounds are susceptible to hydrolysis mediated by enzymes -glucosidases, and the resulting aglycones could be subsequently directed towards different metabolic pathways in plants. Function of two -D-glucosidases (named CeBGlu1 and CeBGlu2) from centaury (Centaurium erythraea Rafn; fam. Gentianaceae), belonging to the glycoside hydrolase 1 (GH1) family, was confirmed using in vitro assays with recombinant proteins, following their heterologous expression in E. coli and His-tag affinity purification. Although they show slightly differential substrate preference, both isoforms display high specificity towards SGs and the organ-specific distribution of transcripts was positively correlated with the content of SGs in diploid and tetraploid C. erythraea plants. Transient overexpression of CeBGlu1 and CeBGlu2 in C. erythraea leaves induced changes in metabolite profiles. The effectiveness of transgene overexpression has been altered by plant ploidy. UHPLC/DAD/()HESIMS2 profiling of leaves of diploid and tetraploid C. erythraea genotypes revealed that the amounts of major SGs; sweroside, swertiamarin, and gentiopicrin was decreased in agroinfiltrated leaves, especially when CeBGlu1 and CeBGlu2 were co-expressed with transgene silencing suppressor p19. The work demonstrates that in planta metabolic engineering adopting transient overexpression of CeBGlu1 and CeBGlu2 is a suitable tool for the modulation of SGs content and glucosides/aglycones ratio, which might have substantial effects on overall phytochemistry of C. erythraea.